El Origen De La Vida Y La Naturaleza Humana En Las Creencias De La Población En General - Bautista, Jesús Silva; Escobar, Venazir Herrera; Miranda, Rodolfo Corona (European Scientific Journal, ESJ, 2016)
Different explanations that have been created around the origin of the universe, human nature and the role of human beings. These explanations have been founded primarily on religious, philosophical and scientific responses based on the belief system. Prior to this premise, it became necessary to investigate what were the beliefs concerning the origin of life and the nature of the human population. Taking into consideration this objective there was a selected sample of 600 people from the general population who answer the five-point Likert type survey. Through statistical tests and validated instrument, it performed comparisons between the beliefs of people according to their sex, educational background, age and marital status. The statistical results showed significant differences between beliefs about the origin of life and human nature in the general population in terms of gender, educational background, age and marital status. Based on the results, the role of beliefs on the behavior of people is basically characterized by how knowledge is acquired on the basis of their theory and practice. Through these means, they know each other’s processes, scientific and nonscientific principles; and assisted on structuring their interaction with reality, the world, their peers and themselves.